Antimicrobial and cytotoxic activity of Macrophomina phaseolina isolated from gummosis infected citrus reticulata (Chittagong University Journal of Biological Sciences, 2013)
Macrophomina phaseolina is one of the pathogenic organisms of gummosis disease of orange tree (Citrus reticulata). The pathogen was identified from the observation of their colony size, shape, colour, mycelium, conidiophore, conidia, hyaline, spore, and appressoria in the PDA culture. The crude chloroform extracts from the organism showed antibacterial activity against a number of Gram positive and Gram-negative bacteria. The crude chloroform extract also showed promising antifungal activity against three species of the genus Aspergillus. The minimum inhibitory concentration (MIC) of the crude chloroform extract from M. phaseolina against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Shigella sonnie were 128 ?gm, 256 ?gm, 128 ?gm and 64 ?gm/ml respectively. The LD50 (lethal dose) values of the cytotoxicity assay over brine shrimp of the crude chloroform extract from M. phaseolina was found to be 51.79 ?gm/ml. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13378 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):125-133, 2010